Gait Speed Modulations Are Proportional to Grades of Virtual Visual Slopes—A Virtual Reality Study - Benady, Amit; Zadik, Sean; Zeilig, Gabriel; Gilaie-Dotan, Sharon; Plotnik, Meir (Frontiers in Neurology, 2021)
Gait is a complex mechanism relying on integration of several sensory inputs as vestibular, proprioceptive and visual cues to maintain stability while walking. Often humans adapt their gait to changes in surface inclinations, and this is typically achieved by modulating walking speed according to the inclination in order to counteract the gravitational forces, either uphill (exertion effect) or downhill (braking effect). The contribution of vision to these speed modulations is not fully understood. Here we assessed gait speed effects by parametrically manipulating the discrepancy between virtual visual inclination and the actual surface inclination (aka visual incongruence). Fifteen healthy participants walked in a large-scale virtual reality (VR) system on a self-paced treadmill synchronized with projected visual scenes. During walking they were randomly exposed to varying degrees of physical-visual incongruence inclinations (e.g. treadmill leveled & visual scene uphill) in a wide range of inclinations (-15 to +15). Approximately linear relation between the relative change in gait speed and the anticipated gravitational forces associated with the virtual inclinations was observed. Mean relative gait speed increase of 7%, 11% and 17% were measured for virtual inclinations of +5°, +10° and +15°, respectively (anticipated decelerating forces were proportional to sin[5°], sin[10°], sin[15°]). The same pattern was seen for downhill virtual inclinations with relative gait speed modulations of -10%, -16% and -24% for inclinations of -5°, -10° and -15°, respectively (in anticipation of accelerating forces). Furthermore, we observed that the magnitude of speed modulation following virtual inclination at ±10° was associated with subjective visual verticality misperception. In conclusion, visual cues modulate gait speed when surface inclinations change proportional to the anticipated effect of the gravitational force associated the inclinations. Our results emphasize the contribution of vision to locomotion in a dynamic environment and may enhance rehabilitation strategies for neurological disorders associated with gait impairments.